Kinetic disposition of ursolic acid in rats - Rosangela Peccinini; Manuel Alzate; Marco Ferraz; Taisa Franchin; Jonata Oliveira; Carol Candido; Junior Furini; Sergio Albuquerque (Mazandaran University of Medical Sciences, 2018)
Benznidazole and nifurtimox are two drugs that are used to treat trypanosomiasis. Ursolic acid (UA) reportedly acts against trypomastigotes and intracellular amastigotes of Trypanosoma cruzi. Accordingly, it is expected to have therapeutic benefits in the treatment of trypanosomiasis. Therapeutic application of a compound requires the investigation of its pharmacokinetic properties in order to obtain relevant information to design the in vivo assays and dose regimen. Regarding this, the current study aimed to evaluate the pharmacokinetic profile of UA administered to rats at different doses and routes (i.e., 1 mg/kg intravenously and 20 and 50 mg/kg orally). According to the results, the oral bioavailability was significantly different between the two groups that orally received the UA doses of 20 mg/kg (2.8%) and 50 mg/kg (1.55 %). The result suggests the interference of the poor aqueous solubility of UA on its absorption process. The pharmacokinetic parameters related to the distribution and elimination were similar. Accordingly, it can be concluded that at this dose range, there is no saturation in this process rendering a linear the kinetics. The pharmacokinetic properties of UA were observed in this study indicated that the improvement of water solubility in this medicine through pharmacotechnical resources would be a great utility for its oral bioavailability and development of a product with the potential therapeutic application. The oral administration of this new pharmaceutical formulation should be investigated in future studies.